1985
DOI: 10.1111/j.1464-410x.1985.tb06291.x
|View full text |Cite
|
Sign up to set email alerts
|

Allopurinol Treatment of Renal Calcium Stone Disease

Abstract: Thirty-one calcium stone patients were treated with 300 mg allopurinol daily during a mean follow-up period of 2 years. They were also given advice on diet and fluid intake. The effects on the recurrence rate of stones were compared with the effects on the recurrence rate in 43 calcium stone patients who were given similar advice on diet and fluid intake but were not treated with allopurinol. In both groups there was a reduction in the recurrence rate but no difference between patients treated with allopurinol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

1986
1986
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…In two open studies Coe and Raisen showed a significant reduction in the risk of calcium oxalate stone formation in hyperuricosuric patients treated with allopurinol [46,47], but these results have not been confirmed in other studies [48–50].…”
Section: Allopurinolmentioning
confidence: 99%
“…In two open studies Coe and Raisen showed a significant reduction in the risk of calcium oxalate stone formation in hyperuricosuric patients treated with allopurinol [46,47], but these results have not been confirmed in other studies [48–50].…”
Section: Allopurinolmentioning
confidence: 99%
“…Rose et al [34] changed urate concentrations of urine samples without any effect on oxalate crystal for mation. Uric acid excretion can be reduced to almost 50% by a daily intake of 300 mg allopurinol [13,37].…”
Section: Allopurinolmentioning
confidence: 99%
“…Controverse data exist in the literature concernig the frequency of hyperurico suria in calcium stone formers [11,13]. A critical study of Fellstrom et al [13] does not reveal a different rate of hyperuricosuria between healthy persons and calcium stone formers.…”
Section: Allopurinolmentioning
confidence: 99%
“…Review of this literature demonstrates a paucity of evidence. In one frequently cited article, a nonrandomized trial, 31 patients were treated with allopurinol, and 43 patients served as untreated controls for recurrent calcium stones (9). Overall, patients who were treated with allopurinol had a recurrence rate of 49% (15 of 31), whereas the control patients, who were not treated with allopurinol, had a recurrence rate of 40% (17 of 43).…”
Section: Febuxostatmentioning
confidence: 99%